Coastal environmental profile of Olango Island, Cebu, Philippines - Sotto, Filipina B.; Gatus, Joey Ll; Ross, Michael A.; Portigo, Ma. Fe. L.; Freire, Francis M. (CRMP, 2001)
CRMP Document No. 28-CRM/2001